SUBJECT-CENTRED CONTENT OF HIGHER EDUCATION AS A FACTOR IN THE EFFECTIVENESS OF PROFESSIONAL TRAINING OF A SPECIALIST - I. A. Leskova (Russian State Vocational Pedagogical University, 2018)
Introduction. Nowadays, extensive processes of globalization, informatization and virtualization have captured all spheres of modern life. These processes require the transition from the traditional knowledge-reproductive training of specialists to the activity focused model in higher school. To implement such a transition, it is necessary to reconsider the organization and methods for student knowledge acquisition of the content of educational programs. The transition has to be centred on the subject of development and knowledge.The aim of the paper is to discuss methodological aspects related to the construction of subject-centred content of higher education and to show its pedagogical capabilities.Methodology and research methods. The methodological framework of the study is performed with the involvement of the regulators of human cognitivetransformational activity, based on the post-non-classical paradigm of cognition; the key principles of the competency-based, activity and personal-centred approaches to training. Theoretical, discursive types of the analysis, content analysis, modelling of pedagogical systems and processes were used to design a conceptual plan of the research and develop its empirical base. Methods of the comparative analysis, synthesis and generalization of practical experience were applied at the stage of an experiment; the hypertext training program was applied during approbation of the developed model for training content.Results and scientific novelty. The essence of the subject-centred approach to designing the content of the higher education was summarized. It is noted that a cognitive component of vocational training is transformed to semantic reality by means of the subject-centred approach. The key concepts of "subject", "subjectivity" and "subject experience" were clarified from the didactic point of view. The research demonstrates the fundamental difference of the content of a new type from its traditional model where it is considered as an object of acquisition, and from the understanding of the content in the activity concept which provides a way (principle) of activity as its elementary unit. A basic unit of the subjectcentred content of the vocational training is the information resource to be transformed by the subject of the education (a student) to personal knowledge through the following this occupation. The student is a self-conscious member of the information and communication process. Based on the subject and author's representations and estimations which provide constructive interaction with the dynamically changing environment, a future expert generates information relying on wellknown knowledge and learns to apply it in a concrete context, getting social, cultural and professional experience. In this regard, a teacher is not an educational content carrier, but a network of hypermedia texts with architectonic-structural points (information hubs) of axiological knowledge. The role of the teacher consists not in formal transfer of the factual material, but assistance with student independent designing and realization of productive capabilities of students. The two-tiered structure of information resource was described. This structure is caused by the unity of the principles of fundamental nature and professional orientation. The script model of the student experience is schematically shown; the logic of training has to comply with the model outlined. The model of subject-centred content of education demonstrating its procedural character and activity form is presented.Practical significance. The author has proposed a new system organization of the content of higher education using the possibilities of hypertext systems. The proposed system can become the basis for the self-development of future professionals, their mobility in the labour market and the maximum self-realization in the chosen sphere of employment.